Implementasi Sistem Informasi Tagihan Dengan Menggunakan Odoo Pada Toko Tridewi - Marini Alifia; lutfi Abdillah; Muhammad Rusli (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
Tridewi store is a self-managed business without any assistance from government funds which is engaged in imported lamps and paintings. This self-started business located in Kebon Bawang, North Jakarta. The problem that exist at the Tridewi Store is the billing process and recording sales transactions, which are still done conventionally or the store is still using the manual method where payment notes and notebooks are still used. so that the conventional method used is still less effective because the data in the book could potentially lost due to human error and environmental factors. This study aims to create a billing and sales recording system could simplify the Tridewi Store business process. The results of this research will be carried out by implementing an ERP system using the Odoo application with the Invoicing module using the Waterfall method, which will support the ERP system running.